Multispecies Pasts and the Possibilities of Multispecies Futures in the Age of the Anthropocene - Ivana Živaljević (Etnoantropološki Problemi, 2021)
The Anthropocene emerges as an aftermath of the long-held, pervasive belief in human exceptionalism, and a wake-up call to reconsider our being in the world as entangled with a plethora of other living selves. Along with ecological and social challenges facing all life on Earth, the very boundaries between Nature and Culture, biological and social, human and nonhuman are being destabilized. From an archaeological perspective, particularly relevant is the understanding of diachronic change through shifting webs of interspecies relations (sensu Tsing). By engaging with various strands of thought within archaeology, anthropology, ecology and ethology, this paper aims to offer a more inclusive, multispecies view of the past. Ultimately, a consideration of human and nonhuman histories as entangled, bears important implications for multispecies futures.